Understanding the professional buyer : what every sales professional should know about how the modern buyer thinks and behaves - Cheverton, Peter (Kogan Page, 2011)
Understanding the Professional Buyer is a practical guide for sales professionals. Providing insight into the behaviour and strategies of buyers it Includes guidance on; motivations and rewards, purchasing analysis and negotiation.